2021
DOI: 10.1098/rspb.2021.0650
|View full text |Cite
|
Sign up to set email alerts
|

And thereby hangs a tail: morphology, developmental patterns and biomechanics of the adhesive tails of crested geckos ( Correlophus ciliatus )

Abstract: Among the most specialized integumentary outgrowths in amniotes are the adhesive, scale-like scansors and lamellae on the digits of anoles and geckos. Less well-known are adhesive tail pads exhibited by 21 gecko genera. While described over 120 years ago, no studies have quantified their possible adhesive function or described their embryonic development. Here, we characterize adult and embryonic morphology and adhesive performance of crested gecko ( Correlophus ciliatus ) tail pads. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 64 publications
(133 reference statements)
0
11
0
Order By: Relevance
“…The replicates fabricated without APS showed a smaller average height for the setae (≈12 µm, measured from n = 10 setae), while those fabricated with APS REM showed a larger average height for the setae (≈22 µm, measured from n = 10 setae), which was consistent with previously reported seta height measurements for gecko feet. [ 28 ] The setae in shed skin exhibited a smaller average height (≈17 µm) than those replicated by APS REM, which could be attributed to the shrinkage of the shed skin by drying. The aspect ratio of the setae replicated by APS REM was 16, indicating that APS REM could replicate features with an aspect ratio of at least 16 using the PVS.…”
Section: Resultsmentioning
confidence: 98%
“…The replicates fabricated without APS showed a smaller average height for the setae (≈12 µm, measured from n = 10 setae), while those fabricated with APS REM showed a larger average height for the setae (≈22 µm, measured from n = 10 setae), which was consistent with previously reported seta height measurements for gecko feet. [ 28 ] The setae in shed skin exhibited a smaller average height (≈17 µm) than those replicated by APS REM, which could be attributed to the shrinkage of the shed skin by drying. The aspect ratio of the setae replicated by APS REM was 16, indicating that APS REM could replicate features with an aspect ratio of at least 16 using the PVS.…”
Section: Resultsmentioning
confidence: 98%
“…This could indicate that the morphology of this species is most adapted to environments with dense vegetation. Unlike H. turcicus and T. mauritanica, E. europaea has a prehensile tail bearing adhesive pads with sensory capabilities (Griffing et al 2021) found in many species of arboreal geckos (Bauer 1998; Bauer & Menegon 2006). From an evolutionary point of view, a tail can act as a fifth limb, facilitating both balance when resting and slow climbing within densely vegetated habitats on the ground and in the upper forest strata (Jusufi et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper by Griffing et al 60 examined maximum digital adhesion force across a range of body sizes of C. ciliatus on the same substrate used in our study. Using their scaling equation ( Adhesion = 1.041(body mass) – 0.69 ), the crested geckos in our study could generate a maximum frictional adhesive force of approximately 10 N with a single forelimb.…”
Section: Discussionmentioning
confidence: 99%